Adduct Formation of Nickel(II) Chelates of 4-Methyl and 2- Methyl 8-Quinolinols with Heterocyclic Nitrogen Bases - Suresh, T.; Math, K.S.; Kulkarni, V.H. (Asian Journal of Chemistry, 2010)
The formation constants of the heterocyclic N-base adducts of the nickel(II) chelates of 4-methyl and 2-methyl-8-quinolinone have been determined spectrophotometrically. Monodentate nitrogen bases gave diadducts. The formation constants of adducts of nickel-2-methyl-8-quinolinate are higher than those of nickel-4-methyl-8-quinolinate. Dibasic ligands such as 1,10-phenanthroline, 2,2´-bipyridyl etc. form monoadducts with nickel(II) chelates of 4-methyl and 2-methyl-8-quinolinol. The formation constants of these adducts are significantly high indicating the bidentate nature of the dibasic ligands, thus satisfying the hexacoordination of nickel.